The Role of Waqf Literacy on Interest in Cash Waqf : Scooping Review - Kuswanto, Didik Heri; Rahayu, Yayuk Ngesti; Rohman, Taufik Noor (PT FORMOSA CENDEKIA GLOBAL, 2024)
This scoping review was carried out to answer questions related to determined research theme. Using various sources of similar research articles that have been grouped systematically, then at conclusions. The main purpose of a scoping review is to find research questions, find relevant research, select research, create data charts, organize, summarize, and report findings from the preparation framework. To map this article, a period of 10 years was used, namely from 8 to 2023. The results of the mapping review show that most studies about cash Waqf influences the desire to donate cash. However, as pointed out by Amin & Abdul Rohman (2021), Hadi et al. (2023) concluded that knowledge about cash waqf does not influence the desire to waqf.